PENUNDAAN PEMENUHAN KEWAJIBAN DEBITUR DALAM PERJANJIAN KREDIT BAGI PELAKU UMKM AKIBAT PANDEMI COVID-19 SESUAI PERATURAN OTORITAS JASA KEUANGAN NOMOR 48 /POJK.03/2020 - Yulinda, Kiki; Tiara, Dora; Mene, Meydianto (Ensiklopedia of Journal, 2023)
The Covid-19 disaster in Indonesia affected all sectors and had a negative impact on economic development, health, education and applicable law. In the legal field, several matters related to the postponement of matters related to contract law based on POJK Number 48 of 2020 Concerning National Economic Stimulus as a Countercyclical Policy on the impact of Covid-19 and the problems faced also concern the postponement of debtor obligations in credit agreements to creditors due to the Covid-19 pandemic. in implementing the relaxation of delays in credit payments by debtors to creditors, in fact it was not carried out in its entirety for every debtor involved in a credit agreement against each creditor. This policy has been established regarding the requirements for debtors who can and are allowed to get credit relaxation for delays in fulfilling achievements during the current pandemic. However, there are still creditors who do not carry out what has been ordered, this is what causes many complaints from the public, who in this case are debtors.Keywords: Credit, Agreement, Delay.